2015
DOI: 10.1177/1937586715575903
|View full text |Cite
|
Sign up to set email alerts
|

Art Viewing Directives in Hospital Settings Effect on Mood

Abstract: The results imply that hospitals may consider offering prompts to help viewers engage with art to enhance mood and exhibiting art that demonstrates empathy for patient suffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Given the diversity in cultures, demographics and individual preferences for artwork, it may be over simplistic to suggest that all individuals experience artwork the same way. 33 The findings indicate that the content and aesthetic qualities of artwork are also important considerations. Although mixed, the studies generally indicated that nature, especially greenery, may be the most stress-reducing.…”
Section: Discussionmentioning
confidence: 99%
“…Given the diversity in cultures, demographics and individual preferences for artwork, it may be over simplistic to suggest that all individuals experience artwork the same way. 33 The findings indicate that the content and aesthetic qualities of artwork are also important considerations. Although mixed, the studies generally indicated that nature, especially greenery, may be the most stress-reducing.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many possible receptive or creative interventions (attending performances, making or viewing visual art or music, etc), visually engaging artwork or visiting museums and galleries have increasingly been employed in partnership with public health initiatives, and healthcare providers in several countries have started to prescribe such activities as psychological health interventions (Camic & Chatterjee, 2013;Chatterjee & Noble, 2017;Packer & Bond, 2010;Thomson et al, 2018;Todd et al, 2017). Among the various effects, empirical evidence has shown that on-site art interactions have been particularly associated with decreased loneliness (Todd et al, 2017;Tymoszuk et al, 2019Tymoszuk et al, , 2020, improved mental health (symptoms of anxiety and depression; Clayton & Potter, 2017;Hansen et al, 2015;Roberts et al, 2011), and increased mood and subjective wellbeing (Bennington et al, 2016;Binnie, 2010;Davies et al, 2016;Hansen et al, 2015;Ho et al, 2015;Karnik et al, 2014;Roberts et al, 2011;Wang et al, 2020). For example, similar to the interventions that will be explored in this paper, Clow and Fredhoi (2006) asked individuals to take a 35-minute visit to an art gallery on their lunch break and found that even short exposures lead to significantly lower self-reported stress (~2.4 points on a pre-/post-visit 10-point scale)…”
Section: Background-(online) Art As a Wellbeing Interventionmentioning
confidence: 99%
“…and cortisol concentrations (see Binnie, 2010;Ho et al, 2015 for similar examples using pre-post assessments).…”
Section: Background-(online) Art As a Wellbeing Interventionmentioning
confidence: 99%
“…Reminding personal experiences in design (Susan, Deana, Michael, & George, 2013;Rainbow, Jordan, Fan, & Judy, 2015;Weiss, Schafer, & Berghorn, 1989;Huhtinen-Hildén, 2014;Chen, Lin, & Liang, 2013) Designing workshops to teach skills and provide hands-on and artistic experiences Conference room space for the presentation of career issues and topics of interest to the elderly about their personal experiences…”
Section: Spatial Independence and Privacymentioning
confidence: 99%